(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
Agricultural policy is generally concerned with the development of agriculture and increasing the rate of production per acre and per man. The study assessed the Nigerian Agricultural policy from 1960 to 2023 by the use of data obtained from World Bank. The objectives of this article were to; identify variables related to agriculture and to assess these variables based on the data obtained. Maximum values added in % GDP (8.83), %GDP of current currency (36.9), in constant 2015 US(9.81), in constant local currency (9.52), in current US (9.88), in annual % growth (55.9) and per worker in constant 2015 US (4669). Agricultural land % of land area accounted a maximum value of 75%, in 2019 with a minimum value of 59% in 1961. Similarly, the arable land in % of land area had a maximum of about 40% in 2019, while agricultural land in sq. km had a minimum of 541,760 sq km in 1960 with a maximum of 686,440 sq. km in 2020. The food production index had a mean of 52.18, while fisheries production had a mean of 384,179, 078 metric tons and agricultural production had a mean of 72,207,875.1 metric tons, cereal yield had a mean of 1,187.9 and a mean crop production index of 52.94. Food exports has declined from a maximum 65% in 1962 to minimum of 0.02% in 2001 with a mean of 15% while food imports had increased with a maximum of 30.6% in 2011, a minimum of 8.1% in 1968 and mean...